THIN FILM-BASED SENSOR FOR MOTOR VEHICLE EXHAUST GAS, NH3, AND CO DETECTION - Sujarwata, S.; Marwoto, P.; Handayani, L. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
A copper phthalocyanine (CuPc) thin film based gas sensor with FET structure and channel length 100 ?m has been prepared by VE method and lithography technique to detect NH3, motor cycle exhaust gases and CO. CuPc material layer was deposited on SiO2 by the vacuum evaporator (VE) method at room temperature and pressure of 8 x10-4 Pa. The stages of manufacturing gas sensor were Si/SiO2 substrate blenching with ethanol in an ultrasonic cleaner, source, and drain electrodes deposition on the substrate by using a vacuum evaporator, thin film deposition between the source/drain and gate deposition. The sensor response times to NH3, motorcycle exhaust gases and CO were 75 s, 135 s, and 150, respectively. The recovery times were 90 s, 150 s and 225, respectively. It is concluded that the CuPc thin film-based gas sensor with FET structure is the best sensor to detect the NH3 gas.Sensor gas berbasis film tipis copper phthalocyanine (CuPc) berstruktur FET dengan panjang channel 100 ?m telah dibuatdengan metode VE dan teknik lithography untuk mendeteksi NH3 gas buang kendaraan bermotor dan CO. Lapisan bahan CuPc dideposisikan pada permukaan silikon dioksida (SiO2) dengan metode vacuum evaporator (VE) pada temperatur ruang dengan tekanan 8 x10-4 Pa. Tahapan pembuatan sensor gas adalah pencucian substrat Si/SiO2 dengan etanol dalam ultrasonic cleaner, deposisi elektroda source dan drain di atas substrat dengan metode vacuum evaporator, deposisi film tipis diantara source/drain dan deposisi gate. Waktu tanggap sensor terhadap NH3, gas buang kendaraan bermotor dan CO berturut-turut adalah 75 s, 135 s,dan 150 s. Waktu pemulihan berturut-turut adalah 90 s, 150 s,dan 225 s. Disimpulkan bahwa sensor gas berstruktur FET berbasis film tipis CuPc merupakan sensor paling baik untuk mendeteksi adanya gas NH3.